2009
DOI: 10.1309/ajcpm7dw0xfhdhny
|View full text |Cite
|
Sign up to set email alerts
|

PAX-2 in the Diagnosis of Primary Renal Tumors

Abstract: The diagnosis of renal cell carcinoma (RCC) remains problematic, especially in the context of metastasis or small needle biopsy specimens. The renal cell carcinoma marker (RCCM) and kidney-specific cadherin (KSC) are considered specific markers for RCC but are expressed preferentially in specific subtypes of RCC of lower grades. This study was aimed at evaluating the usefulness of PAX-2 in the diagnosis of renal tumors and comparing it with that of RCCM and KSC. Immunostaining for PAX-2, RCCM, and KSC was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(7 citation statements)
references
References 32 publications
0
4
1
2
Order By: Relevance
“…The minimal PAX2 labeling we saw in our cases is more difficult to explain but may represent a more exaggerated effect of fixation on this marker, which we and others have found to be less sensitive than PAX8. 22 Although PAX8 and RCC marker antigen have not been studied in the t(6;11) RCC by other groups, we note that Rao et al 7 did not find CD 10 labeling in their small series of t(6;11) RCC, which differs from our results.…”
Section: Discussioncontrasting
confidence: 99%
“…The minimal PAX2 labeling we saw in our cases is more difficult to explain but may represent a more exaggerated effect of fixation on this marker, which we and others have found to be less sensitive than PAX8. 22 Although PAX8 and RCC marker antigen have not been studied in the t(6;11) RCC by other groups, we note that Rao et al 7 did not find CD 10 labeling in their small series of t(6;11) RCC, which differs from our results.…”
Section: Discussioncontrasting
confidence: 99%
“…PAX2 and PAX8 are lineage restricted transcription factors that are known to be expressed in the renal and Müllerian systems, 13,26,29,30,35 and have been found to be expressed in most clear cell and papillary RCC. We found that 14 of 21 Xp11 translocation RCC showed nuclear labeling for PAX2, whereas 16 of 21 showed nuclear labeling for PAX8.…”
Section: Resultsmentioning
confidence: 99%
“…These include tissue-specific transcription factors such PAX2 and PAX8, 13,26,29,30 along with cytoplasmic differentiation markers such as hypoxia-inducible protein 2 (HIG2) 34 and carbonic anhydrase 9 (CA IX). 15,33 Some of these markers have been shown to differentially label the common adult subtypes of renal cell carcinoma, which are clear cell, papillary, and chromophobe RCC.…”
mentioning
confidence: 99%
“…U imunohistohemijskom nalazu svih slu~ajeva tu-mora obuhva}enih našom studijom, dominiralo je citoplazmatsko bojenje, što iznenadjuje, budu}i da se Pax-2, kao transkripcioni faktor, dominantno ispoljava u jedru. Rezultati studije bi se mogli objasniti specifi~noš}u teh-nike imunohistohemijskog bojenja na Pax-2 antigen i po-sledice tkivne endogene avidin-vezuju}e aktivnosti ili ne-specifi~nosti sekundarnog antitela, polimer kompleksa ili drugog relevantnog te-hni~kog faktora, što je u skladu sa studijom Ozcan i saradnika 7 . Pored bubre'nih neoplazmi, ekspresija Pax-2 je uo~ena i u limfomu bubrega.…”
Section: Diskusijaunclassified
“…U adultnom periodu mo'e do}i do ponovne aktivacije Pax-2 transkripcionog faktora, u procesima epitelno-mezenhimne transfor-macije (EMT), proliferacije i transformacije tubularnog epitela i nastanka bubre'ne neoplazme 6 . S obzirom da neoplasti~na transformacija, na gore po-menut na~in, ponavlja proces organogeneze, tumori mogu ispoljiti antigene organ specifi~nih transkripcionih fakto-ra, medju njima i Pax-2 antigen, koji mogu poslu'iti kao zna~ajan dijagnosti~ki marker 7 . Mali je broj radova koji se bavio ispitivanjem u~estalosti ispoljavanja Pax-2 antigena medju razli~itim histološkim tipovima tumora bubrega 8 Imunohistohemijsko bojenje je uradjeno posle obrade tkivnih uzoraka u mikrotalasnoj rerni, u citratnom puferu pH 6.0, radi demaskiranja antigena na parafinskim presecima debljine 5µm, nakon deparafinizacije i dehidratacije.…”
unclassified